Combating drug use in competitive sports. An analysis from the athletes' perspective - Striegel, H.; Vollkommer, G.; Dickhuth, H. H. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: Doping has developed into a widespread problem in competitive and high-performance sports due to increasing professionalism in, and commercialization of sports. In contrast, governments and sports organizations have limited financial resources to support all competitive sports. Therefore, further improvement of anti-doping measures can only be achieved through the inclusion and active participation of the athletes themselves. METHODS: In this study, 101 German athletes who are subject to national and international anti-doping tests were asked if doping in sports should be combated, and which anti-doping measures appeared effective from an athlete's perspective. RESULTS: Ninety-eight point zero two per cent of those ques-tioned felt that measures should be taken against doping in sports. Improved methods of detection and more information on the health risks were favored, as opposed to more severe punishments. In addition, more than two thirds of the athletes supported the introduction of an anti-doping law. The desire for more frequent drug testing was also expressed, despite the distinct invasion of the athletes' privacy. CONCLUSIONS: An anti-doping law, as requested by the athletes, should include measures for educating the public about the health risks involved with doping. In addition, such a law would also make it possible to develop suitable methods of detection.